If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20p + 20p + -12p = -12 Combine like terms: -20p + 20p = 0 0 + -12p = -12 -12p = -12 Solving -12p = -12 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '-12'. p = 1 Simplifying p = 1
| 4x+23=10x-1 | | -80-15v=-42 | | 18x-5=16x+7 | | (4x+23)+(10x-1)=180 | | -[4x+(6x+5)]=1-(5x+8) | | 2(6+b)=28 | | 13q+2q+-14+1=17 | | 3k^2+8k-16=0 | | 3y+x=33 | | 3x^3+2x-28=0 | | 8q+3q+-6q+-2q+-6q=18 | | 2n-n=16 | | -8x=-6-7x | | 12n^2-75=0 | | 13p+-9p+5p-13p=14 | | -2j+16j+-17j+2j=9 | | 6+7x=9x-8 | | -5.7=k+(-3.1) | | 8h-7h=3 | | x^4+4x^2+4-X^2-2=12 | | -200.00+-150.00=2 | | 0.22f+0.22f=13.2+0.22f | | 6(-8)+4y=-16 | | -5x=-4x-6 | | 7x-17=x+6 | | 4(5t-23)-1=67 | | K+9=-26 | | -4f+1=7-3f | | -12.00+3.00x=2 | | (x*6+8)*3-15x=7 | | 13t-3t=20 | | 7(2x+1)=49 |